Association between diabetes mellitus and trochanteric bone mineral density in individuals with osteoporotic fractures: a retrospective study - Guo, Shao-han; Xu, Jian; Xu, Min-zhe; Li, Chong; Gong, Ya-qin; Lu, Ke (Frontiers in Medicine, 2024)
BackgroundThe relationship between diabetes mellitus (DM) and bone mineral density (BMD) in patients with osteoporotic fractures (OPFs) remains complex and heterogeneous, specifically between the genders. This study aimed to explore the association between diabetes status and trochanteric BMD in a cohort of patients with OPFs and elucidate the differences between male and female patients.MethodsThis retrospective analysis was performed on 710 admitted patients aged 50 years or older with OPFs. In this study, the exposure variable was diabetes status. Trochanteric BMD comprised the dependent variable. While controlling for covariance influences, generalized estimating equations (GEE) were applied to examine the independent link between diabetes status and trochanteric BMD in OPFs patients. Moreover, a subgroup analysis was also conducted to validate the result’s stability.ResultsA substantial positive association was noted between diabetes status and trochanteric BMD in diabetic patients, as determined by the fully adjusted model (β = 0.017, 95% CI 0.001 to 0.033, p = 0.035). Furthermore, the sex-specific analysis showed a significant positive relationship between diabetes status and trochanteric BMD in male patients (β = 0.040, 95% CI 0.006 to 0.075, p = 0.022), whereas no significant relationship was observed in female patients (β = 0.010, 95% CI −0.008 to 0.028, p = 0.256).ConclusionThis study highlighted the significant sex differences in the impact of diabetes on trochanteric BMD among patients with OPFs. The male diabetic patients had higher trochanteric BMD than their non-diabetic counterparts; however, this association was not evident in female patients. Further research is necessary to understand the underlying mechanisms that contribute to these sex-specific differences and to evaluate the clinical implications of managing fracture risk in diabetic patients.